Treatment of Patients with the Malposition of Individual Teeth in Patients with Sagittal Occlusion Anomalies (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the present study was to improve the efficiency of complex orthodontic treatment of malposition of teeth in patients with sagittal occlusion anomalies. A limited range of orthodontic appliances and methods of treatment of teeth malposition in patients with sagittal occlusion anomalies provided the rationale for further investigation of this anomaly. During the study, such diagnostic methods as photometry and anthropometry of the jaws and dental rows, X-ray methods (orthopantomography, teleradiography), thermography, electroneuromyography, and rheovasography were used. The treatment was based on the new method and appliance proposed by the authors. The inclusion of the new method and appliance into the complex orthodontic treatment of teeth malposition in patients with sagittal occlusion anomalies after the diagnostic procedures reduced the duration of orthodontic treatment in both active and retention periods of treatment, as well as contributed to the stable positive treatment outcome and improved the quality of life of patients who received complex orthodontic therapy. The application of new appliances proposed by the authors for the treatment of the specified anomaly significantly increased the efficiency of the treatment and improved the quality of the treatment results. The materials presented in this article can have practical value for practicing orthodontists.